2023
DOI: 10.1021/acsaem.3c00177
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Density Lithium–Sulfur Batteries Based on Carbonaceous Two-Dimensional Additive Cathodes

Abstract: The increasing demand for electrical energy storage makes it essential to explore alternative battery chemistries that overcome the energy-density limitations of the current state-of-the-art lithium-ion batteries. In this scenario, lithium–sulfur batteries (LSBs) stand out due to the low cost, high theoretical capacity, and sustainability of sulfur. However, this battery technology presents several intrinsic limitations that need to be addressed in order to definitively achieve its commercialization. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The composition of the S@KJ600-ResFArGO sulfur-positive electrode used on lithium-sulfur gel polymer electrolyte cells comprises 64 wt.% sulfur (S 8 , ≥99%, Sigma-Aldrich, Madrid, Spain), 26 wt.% of carbonaceous materials, and 10 wt.% of binder compounds. The carbons used in this electrode are 16 wt.% of commercial Ketjenblack ® EC-600JD (KJ600, Nouryon, Barcelona, Spain) and 10 wt.% of an in-house made graphene-based activated carbon, ResFArGO, whose synthesis and properties are detailed elsewhere [ 55 ]. In order to ensure good intimate contact between the active material and the conductive carbons, a melt–diffusion process at 155 °C for 12 h was carried out on the mixture to infiltrate sulfur into the different carbons.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of the S@KJ600-ResFArGO sulfur-positive electrode used on lithium-sulfur gel polymer electrolyte cells comprises 64 wt.% sulfur (S 8 , ≥99%, Sigma-Aldrich, Madrid, Spain), 26 wt.% of carbonaceous materials, and 10 wt.% of binder compounds. The carbons used in this electrode are 16 wt.% of commercial Ketjenblack ® EC-600JD (KJ600, Nouryon, Barcelona, Spain) and 10 wt.% of an in-house made graphene-based activated carbon, ResFArGO, whose synthesis and properties are detailed elsewhere [ 55 ]. In order to ensure good intimate contact between the active material and the conductive carbons, a melt–diffusion process at 155 °C for 12 h was carried out on the mixture to infiltrate sulfur into the different carbons.…”
Section: Methodsmentioning
confidence: 99%
“…The Li–S battery has gained enormous attention in energy storage technologies as a result of its higher energy density and economical and eco-friendly nature. One of the key components is sulfur (S), which is an abundant element and contributes to the reduction of the cost of this battery. Sulfur is light enough to reduce the overall weight and increase the energy density of the battery. However, as a result of the poor electrical conductivity, which can limit the lithium-ion transport rate and dissolution behavior in the electrolyte, researchers are continuously working in the direction of replacing S with material that can show similar or better beneficial properties than S. Various approaches have been employed to resolve these issues. At this stage, 2D-based GO-based materials play a significant role to improve the performance of Li–S batteries because of their ability to hold S and lithium ions during the discharging chemistry and, hence, contribute to the electrochemical stability of S by preventing it from dissolution in the electrolyte. Ji et al have reported immobilized S on quasi-2D GO to prepare a GO–S-based cathode for the Li–S battery.…”
Section: Energy Storage Applicationsmentioning
confidence: 99%
“…1 To tackle these issues, lithium-sulfur (Li–S) batteries with high energy density are a promising alternative, although they struggle with issues like sulfur insulation and instability caused by soluble polysulfides. 2,3 Innovative solutions are essential to enhance the performance and stability of Li–S batteries for practical applications in the future.…”
Section: Introductionmentioning
confidence: 99%